Community structure and infection characteristics of metazoan parasites in house Geckos in Peninsular Malaysia / Hazreen Abdul Jabar - Hazreen , Abdul Jabar (2017)
This study described the metazoan parasite community structure of house geckos from Peninsular Malaysia. Six hundred ninety-two geckos were collected from five gecko species (Hemidactylus frenatus, H. platyurus, H. garnotii, Gekko monarchus and Gehyra mutilata) from eight sites in December 2006 until September 2010. Total of 8094 parasites from nine species were identified. They are ectoparasitic mite (Geckobia bataviensis), pentastomid (Raillietiella frenatus), cestode (Oochoristica javaensis), trematodes (Paradistomum geckonum, Postorchigenes ovatus) and nematodes (Thelandros sp., Spauligodon sp., Pharyngodon sp., Skrjabinodon sp.). Host species, gender and size were analyzed in relations to parasite prevalence, intensity, abundance, and diversity to provide baseline data in studying the effects of parasite infection based on host species, gender and size, and overall parasite community structure. Results showed H. frenatus had the highest abundance and parasite diversity. However, this parasite is not host specific as it had been found in non-gekkonid hosts About 60% of the gecko community comprised of H. frenatus, thus it is more available for infection. Host gender-biased susceptibility is apparent in blood-feeding parasites (R. frenatus and G. bataviensis) where infection in females is more prevalent (p<0.05). Females have higher parasite prevalence and diversity, but males have higher infection intensity, suggesting hormone involvement. Younger geckos (>4 cm of SVL) have low parasite load which may be caused by diet restriction due to gape limitation, less interaction with the environment and other geckos, reducing chance for infection. Infection increased when the gecko grows into reproductive size (4-6 cm of SVL) as the diversity and abundance of its diet, and interaction with the environment, increases. However, as it grows older (<6 cm of SVL), infection decreased as it invests more energy on immune system which then controls parasitic infection. Parasites that spread through autoinfection (nematodes) or direct transfer (mites) thrive in high density host community, evident in island habitats where parasite prevalence and intensity are higher. The northern region of Peninsular Malaysia had higher trematode prevalence and intensity while the central region had higher prevalence and intensity of nematodes, pentastomids, and mites. This suggested that northern region had higher diversity of intermediate hosts while the central region had a dense host community and a higher abundance of pests such as cockroaches. The parasite community structure showed a negative correlation between abundance and numerical density and this can be explained by 1. gecko infection increases, then decreases with age as energy expenditure changes according to priorities at different phases of life, 2. bigger geckos can accommodate higher diversity and abundance of parasites, 3. species richness is not affected by host size as parasites are not age or size specific, only highly opportunistic. R. frenatus is euryxenous and had been recorded accidentally infecting humans. Other parasites from this study are stenoxenous, however parasites such as the oxyurid nematodes may be capable of accidentally infecting hosts apart from geckos as they spread through autoinfection. Therefore, the potential of gecko parasites becoming zoonotic exists. More research into the distribution patterns and the parasitesï¿½ ecology are needed to gauge their potential.